Popular injustice: violence, community, and law in Latin America - Godoy, Angelina Snodgrass (Stanford University Press, 2006)
Examining popular injustice -- Legacies of terror in postwar Guatemala -- Militarization, lynchings, and the legacies of terror -- Modernization, crime, and communities in crisis -- Civil society and the contradictions of neoliberal democracy -- Convergence at the poles (and not at the polls).